Comparison of Ciaglia and Griggs Percutaneous Tracheostomy Techniques – A Biomechanical Animal Study - Ronen, Ohad (Indian J Crit Care Med, 2019)
BACKGROUND AND AIMS: The two most common commercial percutaneous dilation tracheotomy (PDT) sets apply different techniques. Our aim was to investigate the biomechanical properties of these two techniques on an animal model, that simulate a human trachea. MATERIALS AND METHODS: Biomechanical properties of the different steps of the Ciaglia Blue Rhino® and Griggs Portex® techniques were measured on 20 pig cadavers. RESULTS: We found that the use of the two different devices created equal sized openings in the trachea (p >0.05). The force needed to insert the Griggs forceps was 1.8 kg average compared to 2.51 kg using the Ciaglia dilator (p <0.00001). The calculated total energy expenditure in the Ciaglia Blue Rhino® kit was 1.46 times greater than the Griggs Portex® kit (p <0.0001). This was mainly due to the amount of energy required during the final dilator stage, which was 4 times more using the Ciaglia Blue Rhino® dilator than the Portex® Griggs-dilator forceps. CONCLUSION: We conducted a series of biomechanical properties experiments on an animal model of PDT using two popular commercial kits – Griggs Portex® guidewire dilating forceps by Smiths Medical and Ciaglia Blue-Rhino® by Cook Medical. The Ciaglia technique required almost 50% more energy to perform a PDT (p <0.0001), mainly because of the force exerted during the final dilator insertion stage compared to the Griggs forceps. Further research is needed to examine if these properties are related to some of the PDT complications. HOW TO CITE THIS ARTICLE: Ronen O, Rosin I, Taitelman UZ, Altman E. Comparison of Ciaglia and Griggs Percutaneous Tracheostomy Techniques – A Biomechanical Animal Study. Indian J Crit Care Med 2019;23(6):247–250.